EXPRESSION OF PHRASEOLOGICAL UNITS IN COGNITIVE LINGUISTICS - Nafruza Azizova Esanboyevna Samdchti (Galaxy International Interdisciplinary Research Journal, 2023)
Cognitive linguistics is not limited to the theory of knowledge in philosophy, but connects language with thinking and is a deep scientific study of the psychological, biological and neurophysiological aspects of its formation with social, cultural and linguistic phenomena. researches. Cognitive linguistics deals with concepts and conceptual units in psychology. At the basis of the concept concept lies meaning and image.